Design, synthesis and docking study of 5-(substituted benzylidene)thiazolidine-2,4-dione derivatives as inhibitors of protein tyrosine phosphatase 1B - Wang, Zengtao; Liu, Zhiguo; Lee, Woojung; Kim, Su-Nam; Yoon, Goo; Cheon, Seung Hoon (Pergamon Press Ltd., 2014)
A series of novel 5-(substituted benzylidene)thiazolidine-2,4-dione derivatives was designed, and synthesized based on our previous studies. Also their activities were evaluated as competitive inhibitors of protein tyrosine phosphatase 1B (PTP1B). Compounds 6d-6g, 7b, 7c, 7e, 7j, 7k, 7m, 14b and 14e-14f showed potent inhibitory effects against PTP1B, and compound 7e, the most potent among the series, had an IC50 of 4.6 mu M. Also a Surflex-Dock docking model of 7e was studied. Compound 7e showed a negative binding energy of -735 kcal/mol and a high affinity to PTP1B residues (Gly220, Ala217, Arg221, Asp181, Ser216, Cys215, Phe182, Gln262 and Ile219) in the active sites, indicating that it may stabilize the open form and generate tighter binding to the catalytic sites of PTP1B. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: PTP1B; 5-ARYLIDENE-2,4-THIAZOLIDINEDIONES; OBESITY; AGENTS; RISK; MICE